2021
DOI: 10.3389/fbioe.2020.611149
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Computational Analysis of Hemodynamics and Wall Mechanics and Their Interactions in Pulmonary Arterial Hypertension

Abstract: Vascular wall stiffness and hemodynamic parameters are potential biomechanical markers for detecting pulmonary arterial hypertension (PAH). Previous computational analyses, however, have not considered the interaction between blood flow and wall deformation. Here, we applied an established computational framework that utilizes patient-specific measurements of hemodynamics and wall deformation to analyze the coupled fluid–vessel wall interaction in the proximal pulmonary arteries (PA) of six PAH patients and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…This limitation was resolved by coupling the hemodynamics with enclosing wall motion using fluid-structure interaction (FSI) simulations. 16,28,29,38,39 One FSI method involved a coupledmomentum model with the assumption of linearized stiffness for the arterial wall, 35,38,39 while Gutierrez et al 9 used small deformation theory. Su et al 28,29 employed idealized geometries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation was resolved by coupling the hemodynamics with enclosing wall motion using fluid-structure interaction (FSI) simulations. 16,28,29,38,39 One FSI method involved a coupledmomentum model with the assumption of linearized stiffness for the arterial wall, 35,38,39 while Gutierrez et al 9 used small deformation theory. Su et al 28,29 employed idealized geometries.…”
Section: Introductionmentioning
confidence: 99%
“…A vast majority of modeling studies 5,10,11,16,21,38,39 have dealt with pulmonary arterial hypertension (PAH, WHO group I). However, left heart disease (WHO group II) and lung disease (WHO group III) are causative factors for PH in the majority of diagnosed cases.…”
Section: Introductionmentioning
confidence: 99%
“…The PAH is a disease characterized by an elevated resistance in the distal branches of the pulmonary arteries (the microvasculature and the lungs compartment); this condition entails an increase in the working pressure of the right ventricle, possibly causing hypertrophy and failure [ 19 ]. It has been demonstrated that the hemodynamics parameters are significant indicators of PAH; in particular, changes in the right ventricle end-diastolic volume and a decrease of WSS at the proximal part of the pulmonary artery are suggested as a good indicator of PAH severity [ 45 ]. We model the PAH disease by increasing the resistance of microvascolature and lungs compartment: specifically, we quintuplicate the R O U T value with respect to the physiological case choosing .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…11 , the right ventricle pressure-volume loop of both the scenarios. According to the literature the PAH case is characterized by an increase of pressures and volumes [ 19 , 42 , 45 ], corresponding to a decrease of the stroke volume.
Fig.
…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation